Axial structure of hollow cathode DC glow discharge in different burning modes - Lisovskiy, V.A.; Bogodielnyi, I.A.; Yegorenkov, V.D. (Вопросы атомной науки и техники, 2013)
The axial profiles of the electron temperature, plasma concentration and plasma potential in a DC glow discharge in nitrogen with a hollow cathode were registered with probe technique. At low pressure (0.05 Torr) the discharge is shown to burn in a high-voltage (electron-beam) mode when an electron beam is formed inside the cathode cavity. A potential barrier is found near the cathode sheath boundary. At gas pressure starting from 0.15 Torr at low discharge currents a glow mode is observed. At higher current the discharge is burning in the hollow mode in which the cavity is filled with high concentration plasma. A potential well up to 3 V deep is observed near the edge of the cathode cavity. On increasing the gas pressure the depth of the potential well in the cathode cavity decreases and the well disappears at 0.5 Torr.